Why have the recent oil price declines not stimulated global economic growth? - Thomas Theobald; Peter Hohlfeld (Institut für Makroökonomie und Konjunkturforschung (IMK), Hans-Böckler-Stiftung, 2017)
We analyze the global relationship between oil prices, commodity-specific financial marketshocks and economic activity by means of Structural Vector Autoregressive (SVAR) models for the period 1996 - 2015. For the financial market variables in our model, we use a breakdown of G-20 countries into net commodity exporting and importing countries to compute the real exchange rate between the country groups as well as the corresponding interest rate spread. Regarding the discussion about the missing expansionary effects of the recent oil price declines at the global level, our empirical framework tests the following transmission: A downgrading of financial conditions for commodity exporting countries can lead to a more serious decline of their domestic demand as should be expected from the pure income effect of lower export revenues due to lower oil prices. Therefore, missing expansionary effects of the recent oil price declines should not only be traced back to the absence of expansionary monetary policy effects at the zero lower bound in many commodity importing countries, but also to a high dependency of commodity exporting countries on international financial markets. – – In dieser Studie analysieren wir die weltwirtschaftlichen Zusammenhänge zwischen Ölpreisen, Rohstoff-spezifischen Finanzmarktschocks und Weltwirtschaftswachstum mit Hilfe struktureller Vektorautoregressiver (SVAR) Modellen für den Zeitraum von 1996 bis 2015. Für die Finanzmarktvariablen in unserem Modell teilen wir die G-20-Länder in Netto-Rohstoffexportierende und -importierende Länder auf, um die realen Wechselkurse zwischen den Ländergruppen sowie die entsprechenden Zinsspreads zu berechnen. Bezugnehmend auf die Diskussion über die ausgebliebenen expansiven Effekte der jüngsten Ölpreisrückgänge auf die Weltwirtschaft prüfen wir mit Hilfe des empirischen Modells die folgende Transmission: Eine Verschlechterung der finanziellen Bedingungen für Rohstoffexportländer kann zu einem stärkeren Rückgang der Binnennachfrage führen, als es aufgrund des reinen Einkommenseffekt über geringere Exporteinnahmen infolge des niedrigeren Ölpreises zu erwarten gewesen wäre. Daher sollte das Ausbleiben expansiver Wachstumseffekte der jüngsten Ölpreisrückgänge nicht nur auf das Fehlen expansiver geldpolitischer Effekte an der Nullzinsgrenze in vielen Rohstoffeinfuhrländern zurückgeführt werden, sondern auch auf eine hohe Abhängigkeit der Rohstoffausfuhrländer von den internationalen Finanzmärkten
urn:nbn:de:101:1-2017112013581
Keywords: C30; E37; Q43; 330; oil price; interest rate spread; real exchange rate; economic growth; sign restriction